Analysis of Translation Shift of Noun Phrase In The Adventures of Huckleberry Finn Novel By Mark Twain - Ayu Arthia Ningsih (IJELAL (International Journal of English Learning and Applied Linguistics), 2021)
This thesis is entitled An Analysis Of Translation Shift Of Noun Phrase In The Adventures Of Huckleberry Finn Novel by Mark Twain’s. it has two objectives, namely (1) To Identify the types of noun phrase in terms of its constituent parts are used in The Adventures Of Huckleberry Finn Novel and (2) To Identify the types of translation shifts of noun phrase in The Adventures Of Huckleberry Finn Novel. Theory proposed by Catford (1965) about types of Translation Shift and it was combined with theory of Types of Noun Phrase by Quirk, Greenbaum, (1985: 245). The collected data were analyzed by reading the novel and classify the data base on the theory adopted. Based on final result show that the researcher finds 434 data of Noun Phrase found in the novel were Determinative + Head 266 data, Head + Pre-modification 99 data, and Head + Post-modification 69 data. The Types of Translation shift researcher finds 434 data that found in the novel were Translation Shift divided into two categories the first is Level shift its found 52 data and Category Shift is 382 data that divided into four categories the first is Unit Shift 35 data, Structure Shift 279 data, Class Shift 56 data and the last is Intra-system Shift 12 data.